Development of chitosan based nanocomposite film for the wing membrane of biomimetic micro air vehicles (BMAV) / Rubentheren Viyapuri - Rubentheren, Viyapuri (2016)

(untitled)
Biomimetic Micro Air Vehicles (BMAV) are unmanned, micro-scaled aircraft that are bioinspired from flying organisms to achieve lift and thrust by flapping their wings. There are still many technological challenges involved with the designing BMAV. One of these is designing ultra-lightweight materials and structures for the wings that have the mechanical strength to withstand continuous flapping at high frequencies (e.g. 30 Hz for a dragonfly). Insects achieve this by using chitin-based, wing frame structures that encompass a thin, film membrane. The overall objective of this research is to develop an innovative wing membrane for a BMAV, bioinspired from actual dragonfly wings. Chitosan was used as a polymer matrix. Chitin nanowhiskers (CNW) and nanocrystalline cellulose (NCC) were prepared in laboratory and used as reinforcement fillers in the design of two types of nanocomposite membranes. In each type, tannic acid was used as crosslinker for the chitosan matrix. Film samples with different ratios of nanomaterials and crosslinking agent were prepared. The chemical changes, structural properties, and mechanical performance of each sample was measured, analyzed, and compared. Following these initial studies, heat treatment was also investigated to assess its potential for improving the chitosan nanocomposite film. Transmission electron microscopy (TEM) and scanning electron microscope (SEM) confirms the nano-scaled size of nanomaterial produced and reveals the dispersion level of the nanomaterials in the chitosan matrix. Fourier-transform-infrared spectroscopy (FTIR) was used to investigate the molecular interaction of film. X-ray diffraction (XRD) results indicated that the nanocomposite films have a rigid structure. Performance analysis using a universal testing machine (UTM) and nanoindentation machine indicates that, the tensile strength and modulus increase significantly for the crosslinker nanocomposite films. Wettability, moisture content and solubility tests show that the film exhibits elevated water resistant when the additives and heat treatment are introduced. A dragonfly wing frame structure iv was also bio-mimicked and fabricated using a 3D printer. The membrane was applied to these BMAV wing frames by a casting method. A flapping generator was used to produce static, flapping motion on these BMAV wings and an actual dragonfly wing (for comparison). The aeroelastic properties of both the BMAV and actual dragonfly wings were examined using two high speed frame camera. Bending angle, wing tip deflection and wing tip twist angle were analyzed at the flapping frequencies of 30 Hz, 60 Hz and 120 Hz.